Characterization of recombinant inbred lines and QTL mapping associated to the cycle and yield of common bean - Faleiro, Fábio Gelape; Schuster, Ivan; Ragagnin, Vilmar Antônio; Cruz, Cosme Damião; Corrêa, Ronan Xavier; Moreira, Maurílio Alves; Barros, Everaldo Gonçalves de (Pesquisa Agropecuaria Brasileira, 2003)
The objectives of this work were to characterize 154 recombinant inbred lines of common bean by evaluation of quantitative, morphologic, molecular and disease resistance characteristics and to map quantitative trait loci (QTL) associated to the cycle and production of common bean. Using a LOD score of 4.0 and a recombination frequency of 0.40, 43 markers were mapped into nine linkage groups, covering a total recombination distance of 247.8 cM. The distance between adjacent markers varied between 0 and 28 cM with average of 7.3 cM. The linkage groups size varied between 2.3 and 61.2 cM. The anthracnose and rust resistance genes were mapped in the same linkage group. QTL associated to the eight quantitative characteristics were mapped. The phenotypic variance explained by the QTL varied between 14.03% and 40.14%. The results obtained are the basis for the development of specific saturated maps to be used in common bean programs.